Effects of growth and aging on the reference values of pulmonary nitric oxide dynamics in healthy subjects. (13th September 2017) - Högman, M; Thornadtsson, A; Liv, P; Hua-Huy, T; Dinh-Xuan, A T; Tufvesson, E; Dressel, H; Janson, C; Koskela, K; Oksa, P; Sauni, R; Uitti, J; et al.
Abstract: The lung just like all other organs is affected by age. The lung matures by the age of 20 and age-related changes start around middle age, at 40–50 years. Exhaled nitric oxide (FE NO) has been shown to be age, height and gender dependent. We hypothesize that the nitric oxide (NO) parameters alveolar NO (CA NO), airway flux (Jaw NO), airway diffusing capacity (Daw NO) and airway wall content (Caw NO) will also demonstrate this dependence. Data from healthy subjects were gathered by the current authors from their earlier publications in which healthy individuals were included as control subjects. Healthy subjects (n = 433) ranged in age from 7 to 78 years. Age-stratified reference values of the NO parameters were significantly different. Gender differences were only observed in the 20–49 age group. The results from the multiple regression models in subjects older than 20 years revealed that age, height and gender interaction together explained 6% of variation in FE NO at 50 ml s −1 (FE NO50 ), 4% in Jaw NO, 16% in Caw NO, 8% in Daw NO and 12% in CA NO. In conclusion, in this study we have generated reference values for NO parameters from an extended NO analysis of healthy subjects. This is important in order to be able to use these parameters in clinical practice.